Does the Consumer Want to Be Greened? The Place of Green Packaging Applications with Green Supply Chain Function in Consumer Perception - Tüzemen, Adem; Kuru, Özgür (International Journal of Contemporary Economics and Administrative Sciences, 2018)
The aim of this research is to measure the effects of the packages that are presented as a result of the green packaging applications in food products and to the consumers, taking into consideration the environmental, health, quality, reusability and recycling benefits of consumers. For this purpose, a face to face questionnaire was applied to 371 consumers in Giresun province and the data obtained by using SPSS software, frequency analysis, descriptive factor analysis, independent two sample t-test and one-way analysis of variance were applied. Research results show that consumers at the lowest level of education and income group are more concerned with what the product is more about than packaging and they are more price-oriented than packaging. It has been determined that consumers with higher education and income levels have more meaning to packaging and have more environmental sensitivities. In the research, two groups of groups emerged at the point of packaging. Those who define their jobs as unemployed, housewives, retired and without a regular job, and those who define their profession as workers, civil servants, private sector employees and teachers. It was determined that the first group treated the environment and packaging properties by acting as price-benefit oriented, while the second group decided on the opposite direction and shaped the purchasing behaviors.